PERAN HUKUM TAURAT DALAM PERJANJIAN BARU: SUATU PENERAPAN BAGI GEREJA DAN ISRAEL - Samuel Lengkong (Manna Rafflesia, 2026)
The Old Testament and the New Testament are two sides of a continuous history. However, Ephesians 2:15 states that the Law has been abolished. Meanwhile, Matthew 5:17 states that Jesus did not come to abolish the Law. This study uses a qualitative research method with a literature study approach, where library data is reviewed and analyzed to obtain a hypothesis or concept to obtain objective results. The purpose of this study is to discover the actual facts regarding the statement that the Law has been abolished and the implications of the Law for the church and the nation of Israel. The findings in this study are that the Law has been replaced and perfected through the work done by Jesus Christ. The Law is a history of God's faithful love and serves as a warning for both Israel and the Church. The application of the Law for both the church and Israel must be based on faith, love, and Jesus Christ.